2021
DOI: 10.3390/membranes11100762
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Salinity and Abscisic Acid on Lipid Transfer Protein Accumulation, Suberin Deposition and Hydraulic Conductance in Pea Roots

Abstract: Lipid transfer proteins (LTPs) participate in many important physiological processes in plants, including adaptation to stressors, e.g., salinity. Here we address the mechanism of this protective action of LTPs by studying the interaction between LTPs and abscisic acid (ABA, a “stress” hormone) and their mutual participation in suberin deposition in root endodermis of salt-stressed pea plants. Using immunohistochemistry we show for the first time NaCl induced accumulation of LTPs and ABA in the cell walls of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…Further candidates associated with HSW in drought conditions include the lipid-transfer protein (LTP) DIR1, the transcription termination factor MTEF1 and a xyloglucan endotransglucosylase/hydrolase protein. LTPs are thought to be involved in plant defense responses ( Safi et al., 2015 ) and their expression is induced by biotic and abiotic stresses, including disease, salinity, temperature and drought ( Safi et al., 2015 ; Akhiyarova et al., 2021 ; Duo et al., 2021 ; Zhao et al., 2021 ). It is also well established that drought tolerance is regulated by the mitochondrial transcription termination factors (MTERFs).…”
Section: Discussionmentioning
confidence: 99%
“…Further candidates associated with HSW in drought conditions include the lipid-transfer protein (LTP) DIR1, the transcription termination factor MTEF1 and a xyloglucan endotransglucosylase/hydrolase protein. LTPs are thought to be involved in plant defense responses ( Safi et al., 2015 ) and their expression is induced by biotic and abiotic stresses, including disease, salinity, temperature and drought ( Safi et al., 2015 ; Akhiyarova et al., 2021 ; Duo et al., 2021 ; Zhao et al., 2021 ). It is also well established that drought tolerance is regulated by the mitochondrial transcription termination factors (MTERFs).…”
Section: Discussionmentioning
confidence: 99%
“…It was important to find out how bacterial treatment could affect the formation of apoplastic barriers and abundance of aquaporins. Previously, ABA stimulated the formation of apoplastic barriers in pea plants [ 33 ] and increased aquaporins activity in many species [ 8 , 20 , 34 ]. In the present work, immunolocalization showed an increased abundance of ABA in the root sections of the bacteria-treated plants, which was most noticeable in the region of the endodermis and exodermis.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro binding experiments showed that LTPs can bind both saturated and unsaturated free fatty acids (C12–C20) or the fatty acyl chains presented in various molecules as in lysophosphatidylcholine (LPC), phosphatidylglycerol (PG), acyl coenzyme A (CoA), and cerebrosides (galactolipids), and it can bind jasmonic and abscisic acids, prostaglandin B2, molecules of organic solvents, and some drugs [ 18 , 21 , 23 , 24 , 25 , 26 ]. For many LTPs, in vitro binding data show that the proteins lack specificity in binding to ligands.…”
Section: Features Of Plant Lipid-binding and Transfer Proteinsmentioning
confidence: 99%